DOES EDUCATION ENHANCE INTELLECTUAL ABILITY AND COGNITIVE RESERVE? EVIDENCE FOR A SENSITIVE PERIOD. (11th November 2018) - Kremen, W; Beck, A; Gustavson, D; Reynolds, C; Tu, X; Sanderson-Cimino, M; Lyons, M; Franz, C
Abstract: Education, occupational complexity, and engagement in cognitive activities are common indices of cognitive reserve. They are widely considered protective against risk for cognitive decline and dementia, but reverse causation is also possible. To test the reserve causation hypothesis, we examined the impact of several factors on late-midlife cognitive function in 1009 men (average age 62) after controlling for general cognitive ability (GCA) assessed at average age 20. Models included several additional factors that can affect cognition: age; race/ethnicity; childhood socioeconomic status; physical activity; and health status. Outcomes were seven different cognitive abilities/domains. We examined the unique contribution of each factor. Age 20 GCA accounted for an average of 10% of the variance in later cognitive function. Other factors each accounted for an average of <1% of variance. Additional education after the age 20 GCA assessment had little or no effect. Our results support the reverse causation hypothesis, yet prior studies with pre-post comparisons have found that additional education did result in GCA increases. However, baseline assessments in those studies were primarily during childhood or early adolescence. We conclude that the results are consistent with the idea that more education provides an environment that increases genetic potential for cognitive development if it takes place during periods of substantial brain development. When brain development is more nearly complete—as at the age of our baseline GCA assessment and when participants may have gotten additional education—additional education may be more about maintenance or restoration, rather than development, of cognitive function.